Study of the Names of the Qur'an as a Book of Communication: The Perspective of Quraish Shihab in the Interpretation of Al-Mishbah - Putri Zuhra Furna (Jurnal Ilmiah Syi'ar, 2026)
Background: The Qur’an is not only the word of God but also a divine communication book that conveys messages systematically and ethically. This study examines the names of the Qur’an—Al-Qur’an, Al-Kitab, Al-Furqan, Adz-Dzikr, and At-Tanzil—within Tafsir Al-Mishbah by M. Quraish Shihab to understand the communicative function of revelation in human life.Method: Qualitative research using a descriptive-analytical approach through library study. Primary data were taken from Tafsir Al-Mishbah, while secondary data came from related literature. Analytical techniques were used to identify the meaning and communicative function of each name of the Qur’an.Results: Each name of the Qur’an reflects a unique communicative function: Al-Qur’an as a guiding recitation, Al-Kitab as a preserved written document, Al-Furqan as a distinguisher between truth and falsehood, Adz-Dzikr as a moral reminder, and At-Tanzil as an authentically revealed scripture. Quraish Shihab emphasizes that the Qur’an acts as a complete communication medium involving the communicator (God), the message (revelation), and the audience (humans).Conclusion: Through its names, the Qur’an functions as a communication book that not only conveys information but also shapes human awareness, morality, and actions according to cultural and social contexts. Tafsir Al-Mishbah shows that the Qur’an is a lamp that illuminates human life through persuasive and transformative communication.